Hexahedral mesh modification to preserve volume. (December 2018) - Le Goff, Nicolas; Ledoux, Franck; Owen, Steven
Abstract: In this work, we provide a new post-processing procedure for automatically adjusting node locations of an all-hex mesh to better match the volume of a reference geometry. This process is particularly well-suited for mesh-first approaches, as overlay grid ones. In practice, hexahedral meshes generated via an overlay grid procedure, where a precise reference geometry representation is unknown or is impractical to use, do not provide for precise volumetric preservation. A discrete volume fraction representation of the reference geometry M I on an overlay grid is compared with a volume fraction representation of a 3D finite element mesh M O . This work introduces the notion of localized discrepancy between M I and M O and uses it to design a procedure that relocates mesh nodes to more accurately match a reference geometry. We demonstrate this procedure on a wide range of hexahedral meshes generated with the Sculpt code and show improved volumetric preservation while still maintaining acceptable mesh quality. Highlights: Definition of a localized discrepancy. Volume preservation improvement of a mesh. Different kinds of inputs were tested.